The Influence of Human Resource Competence, Accounting Standards and Accounting Systems on the Quality of Financial Reports in the Regional Government of Purwakarta Regency - Siti Robiah Adawiah; Nuryaman Nuryaman (Quantitative Economics and Management Studies, 2023)
This study aims to analyze the role of human resource competence, accounting standards, and accounting systems on the quality of financial reports in the context of local government agencies in Purwakarta Regency, Indonesia. This study uses primary data taken cross-sectionally by distributing questionnaires to the respondents. The population and sample in this study were all employees of the finance section at several SKPDs in Purwakarta Regency, totaling 130 respondents. The findings of this study indicate that human resource competence, accounting standards, and accounting systems partially and simultaneously have a positive effect on the quality of the regional government's financial reports in Purwakarta Regency. This means that this research implies that the government needs to pay attention to several aspects in order to produce good quality financial reports.